Pembuatan Biobriket dari Campuran Bottom Ash dengan Limbah Padat Kelapa Muda Menggunakan Lem Molase sebagai Bahan Bakar Alternatif - Tampubolon, Heriansyah; Muthawali, Dede Ibrahim; Ginting, Zainuddin; Jalaluddin, Jalaluddin; Kusuma, Budhi Santri (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Biobriquettes are solid fuels made from compressed organic residues with adhesives. Bottom ash, a byproduct of boiler combustion at PT Blang Ketumba, and young coconut solid waste both have high calorific value and can be utilized as bio briquettes. This study uses a mixture of young coconut waste and molasses adhesive. The research aims to assess the benefits of these materials in bio briquettes, analyze the composition of bottom ash and young coconut waste, and examine the impact of varying ratios of these materials with molasses adhesive. The biobriquette production process involves mixing bottom ash and coconut waste with 2%, 3%, and 4% molasses adhesive in ratios of 100:0, 75:25, 50:50, 25:75, and 0:100. The resulting biobriquettes are evaluated for moisture, ash content, bulk density, combustion rate, and calorific value. The optimal biobriquette, with 25:75 bottom ash to coconut waste and 4% adhesive, showed 7.6% moisture, 5.9% ash, 14.76% volatiles, 71.74% fixed carbon, 1.74 g/cm³ density, 0.32 cal/sec combustion rate, and 5142 cal/g calorific value, meeting SNI 01-6235-2000 standards.